Rumen bacterial endotoxins and their possible role in the sudden-death syndrome - Nagaraja, Tiruvoor G.; Bartley, E.; Fina, L.; Anthony, H.; Leipold, H. (Kansas State University. Agricultural Experiment Station, 2011)
We have found that rumen bacteria contain endotoxins that are released into rumen fluid. Also rumen fluid from grain-fed cattle contains considerably more free endotoxin than rumen fluid from hay-fed cattle. Injecting cattle with rumen bacterial endotoxins may be involved with such diseases associated with high-grain feeding as the sudden death syndrome.
Keywords: Beef; Endotoxins; Sudden death syndrome